What predicts effectuation preferences Disentangling individual and environmental factors and illuminating decision criteria - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Different ways lead to ambidexterity: Configurations for team innovation across China, India, and Singapore - Deng, Wei; Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli (Journal of International Management)
Keywords: Strategy and Management; Finance; Business and International Management

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Combined Economic and Emission Dispatch of a Microgrid Considering Multiple Generators - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand side management potential of refrigeration appliances - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand-Side-Management for Optimal dispatch of an Isolated Solar Microgrid - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE AFRICON, Nairobi, Kenya)

Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Igor Levit - No Fear! Ein Film von Regina Schilling - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik (https://www.theomag.de/145/hsw24.pdf))

A Methodical Approach to Hybrid Modelling for Contextual Anomaly Detection on Time-Series Data - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Innovative self-learning disturbance compensation for straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Materials Research Proceedings)
Abstract. To increase the sustainability of forming processes such as punch bending, homogenization of the processed semi-finished product is an essential step in the manufacturing process. High-strength wire materials are usually available as strip material before being further processed in a forming process. For storage and transport, the material is coiled onto coils and transported to the customer. During the coiling process, residual stresses and plastic deformation are introduced into the wire. Thus, the final product quality is also influenced by the geometry of the coil. Straightening machines are used in production lines to compensate for these. Once a straightening machine has been set up, the settings for the roll positions are usually not changed. As a result, there is no reaction to material fluctuations, which means that the components to be produced do not meet the dimensional accuracy requirements. This leads to an increase in the rejection rate in manufacturing processes. To reduce the rejection rate, it is necessary to enable dynamic and flexible infeed of the straightening rollers. In this context, an innovative control concept with disturbance compensation was developed for the straightening process. The disturbance compensation uses a disturbance model that predicts the change in bending curvature over the coil radius. With this prediction, the straightening machine can be adjusted specifically. The roller positions are adjusted by a subordinate position control. The additional feedback from measured geometric product properties from the following punching-bending process enables the straightening machine to be adjusted even in the case of unforeseen fluctuations in the material properties. In this way, it is possible to react to any material fluctuations as required. This novel, demand-oriented adjustment of the straightening machine is expected to result in a high increase in the efficiency of the production process and a reduction of the rejection rate.

Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Wer übernimmt Verantwortung für Inklusion? - Kottmann, Brigitte; Lütje-Klose, Birgit; Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Bildungspolitik; Schulentwicklung; Sonderpädagogik

Elektrooptischer Balun und System zur Generierung eines pseudodifferentiellen Signals aufweisend einen solchen elektrooptischen Balun - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Balun, wobei der elektrooptische Balun einen Eingang für ein optisches Eingangssignal (Ein(t)) aufweist, wobei der elektrooptische Balun weiterhin ein 1x2 Multimodeninterferometer (1x2 MMI) und einen Phasenschieber (Δϕ) aufweist, wobei das 1x2 Multimodeninterferometer (1x2 MMI) mit dem Eingangssignal im Betrieb versorgbar ist, wobei der elektrooptische Balun weiterhin ein 2x4 Multimodeninterferometer (2x4 MMI) aufweist, wobei das 2x4 Multimodeninterferometer (2x4 MMI) mit den Ausgangsarmen des 1x2 Multimodeninterferometer (1x2 MMI) verbunden ist, wobei der Phasenschieber (Δϕ) in einem Ausgangsarm des 1x2 Multimodeninterferometer (1x2 MMI) angeordnet ist, wobei im Betrieb an zwei Ausgängen (Eout,1 (t), Eout,4(t)) des 2x4 Multimodeninterferometers (2x4 MMI) ein quasi differentielles optisches Signal anliegt, das mittels einer jeweiligen Photodiode (PD1, PD2) und einem differentiellen Schaltkreis in ein DC-freies elektrisches Signal (Vout) überführt werden kann. Weiterhin betrifft die Erfindung ein System zur Generierung eines pseudeodifferentiellen Signals, aufweisend einen elektrooptischen Balun sowie einen optischen Strahlteiler (OS) sowie einen dual output carrier injection Mach Zehnder Modulator (MZM), wobei der optische Strahlteiler (OS) ein Eingangssignal (IIN) in einen ersten Teil (n) und einen zweiten Teil (1-n) aufteilt, wobei der zweite Teil (1-n) als Eingangssignal (Ein(t)) im Betrieb auf den Eingang des elektrooptischen Baluns geführt wird, wobei der erste Teil (n) im Betrieb als Eingangssignal dem dual output carrier injection Mach Zehnder Modulator (MZM) zugeführt wird, wobei das quasi differentielle elektrische Signal (I1, I2) der Photodioden (PD1, PD2) im Betrieb zur Ansteuerung des dual output carrier injection Mach Zehnder Modulator (MZM) in push pull Konfiguration verwendet wird.